2023
DOI: 10.1088/1361-6501/ace6c5
|View full text |Cite
|
Sign up to set email alerts
|

A novel calibration method for kinematic parameter errors of industrial robot based on Levenberg–Marquard and Beetle Antennae Search algorithm

et al.

Abstract: In this paper, a new kinematic parameter error calibration method based on the Levenberg–Marquard and the beetle antennae search algorithm is proposed to enhance the positioning accuracy of the industrial robot. Firstly, the Modified Denavit–Hartenberg model is chosen to establish the kinematic model for the industrial robot. Secondly, the kinematic parameter errors are calibrated by Levenberg–Marquard algorithm and then obtain the kinematic parameter errors of the industrial robot. Thirdly, these kinematic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The training data and the iteration period are also guaranteed to be constant. The Particle Swarm Optimization algorithm (PSO) [40], Beetle Antennae Search algorithm (BAS) [41], Sparrow Search algorithm (SSA) [42], and MVO-optimized SVM are used with the same image feature parameters and time delay compensation, respectively, and the prediction effect is finally observed using the same set of test data. Since optimization algorithms are generally strongly stochastic, ten sets of tests are performed for each algorithm, and the Wilcoxon sign rank test [43] is performed between the RMSEs of the prediction results of the three comparison algorithms and the RMSEs of the MVO, respectively, to prove the optimization effectiveness of the MVO algorithm.…”
Section: Model Test Resultsmentioning
confidence: 99%
“…The training data and the iteration period are also guaranteed to be constant. The Particle Swarm Optimization algorithm (PSO) [40], Beetle Antennae Search algorithm (BAS) [41], Sparrow Search algorithm (SSA) [42], and MVO-optimized SVM are used with the same image feature parameters and time delay compensation, respectively, and the prediction effect is finally observed using the same set of test data. Since optimization algorithms are generally strongly stochastic, ten sets of tests are performed for each algorithm, and the Wilcoxon sign rank test [43] is performed between the RMSEs of the prediction results of the three comparison algorithms and the RMSEs of the MVO, respectively, to prove the optimization effectiveness of the MVO algorithm.…”
Section: Model Test Resultsmentioning
confidence: 99%
“…Experiments on diverse datasets validate its efficacy. More studies on the improved BAS algorithm can be found in the literature (Fan et al 2023.…”
Section: Othersmentioning
confidence: 99%